Nonlocal diffusion equations with dynamical boundary conditions. (June 2020) - Berná, Pablo M.; Rossi, Julio D.
Abstract: In this paper we study nonlocal problems that are analogous to the local ones given by the Laplacian or the p − Laplacian with dynamical boundary conditions. We deal both with smooth and with singular kernels and show existence and uniqueness of solutions and study their asymptotic behaviour as t goes to infinity.